Parents’ attitudes towards the use of distance learning in light of the Corona pandemic - Salem, Heba Tawfeq; Wahbeh, Fatima Abd Alkareem (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the attitudes of parents towards the use of distance learning in light of the Corona pandemic, and to achieve the objectives of the study, the descriptive approach was used, whereby the questionnaire was used as a tool for collecting information, and standards of validity and reliability of the study instrument were extracted according to scientific principles. The study sample was chosen randomly, which consisted of parents of (N=250). The results of the study showed that the arithmetic means and standard deviations related to the attitudes of parents towards the use of distance learning in light of the Corona pandemic that the arithmetic means ranged between low, medium, high and very high, and the results also showed that there were no statistically significant differences in the attitudes of parents towards the use of distance learning in light of the Corona pandemic due to the variables of father’s educational level, the mother’s educational level, the number of children enrolled in school and per family, while there were statistically significant differences for Parents’ work variable in favor of the parents category. The study recommends that the school should be keen on continuous communication with parents to follow the course of the educational process remotely in light of the Corona pandemic.